Pengaruh Konsumsi Susu Kedelai terhadap Kontrol Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe 2 di Dusun Tampungan dan Dusun Besalen Bantul Yogyakarta - ROHMAH, Anna Miftahul (STIKES 'Aisyiyah Yogyakarta, 2009)
This research was aimed at identifying the effect of soy bean milk consumption on the control of blood glucose level on the type II diabetes mellitus patients in Besalen and Tampungan villages. There were 10 people used as the samples, 5 people for the control group and other 5 for the experiment group.The method of the research was the Quasi Experiment,with the approach of Non Equivalent Pretest Posttest. The gained data was then examined using the statistic test by applying t-test dependent. The result showed that P value (0,009) < ? (0,05), it can be concluded that there is found effect of soybean milk consumption on the control of blood glucose level on the type II diabetes mellitus patients.